Determinants and Macroeconomic Impact of Remittances in Sub-Saharan Africa - Singh, Raju (IMF Working Papers; Working Paper ;, 2009)
The paper investigates the determinants and the macroeconomic role of remittances in sub-Saharan Africa, assembling the most comprehensive dataset available so far on remittances in the region and incorporating data on the diaspora. It finds that remittances are larger for countries with a larger diaspora or when the diaspora is located in wealthier countries, and that they behave countercyclically, consistent with a role as a shock absorber. Although the effect of remittances in growth regressions is negative, countries with well functioning domestic institutions seem nevertheless to be better at unlocking the potential for remittances to contribute to faster economic growth.